BIOLOGICAL TREATMENT OF PSORIASIS – MECHANISMS OF ACTION, CLINICAL EFFICACY AND SAFETY OF THERAPY - Przemysław Piskorz; Weronika Sobota; Patryk Biesaga; Olaf Jadanowski; Kamil Łebek; Alicja Bury; Daria Litworska-Sójka; Bartosz Komsta; Julia Lipiec; Wojciech Pabis (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: Psoriasis is a chronic autoimmune skin disease that significantly reduces patients’ quality of life. The coexistence of comorbidities and persistent lesions makes treatment challenging. This review summarizes current knowledge on the mechanisms, efficacy, and safety of modern therapies, focusing on TNF-α, IL-17, IL-23 inhibitors, and apremilast as a PDE4 inhibitor.Review methods: This narrative review is based on publications from the last five years, including phase III clinical trials, meta-analyses, and updated dermatological guidelines, retrieved from PubMed and Google Scholar.Summary of current knowledge: Psoriasis management increasingly relies on targeted therapies. TNF-α inhibitors (infliximab, adalimumab, certolizumab) are effective but may cause serious adverse effects. IL-17 inhibitors (secukinumab, ixekizumab, brodalumab) provide rapid responses with generally favorable safety, though caution is required in patients with inflammatory bowel disease. IL-23 inhibitors (guselkumab, risankizumab, tildrakizumab) combine high efficacy with good tolerability, making them among the most promising options. Apremilast, a PDE4 inhibitor, is less potent but safe and useful in patients unsuitable for immunosuppression.Summary: Biological therapies have transformed psoriasis care, offering improved symptom control, quality of life, and reduced risk of joint involvement. These targeted agents ensure high remission rates while maintaining safety. Ongoing research and individualized approaches may further establish biological therapy as a mainstay of dermatological practice.